Insights into the molecular profiles of adult and paediatric acute myeloid leukaemia. Issue 9 (11th February 2021) - Aung, Myint Myat Khine; Mills, Megan L.; Bittencourt‐Silvestre, Joana; Keeshan, Karen
Abstract : Acute myeloid leukaemia (AML) is a clinically and molecularly heterogeneous disease characterised by uncontrolled proliferation, block in differentiation and acquired self‐renewal of hematopoietic stem and myeloid progenitor cells. This results in the clonal expansion of myeloid blasts within the bone marrow and peripheral blood. The incidence of AML increases with age, and in childhood, AML accounts for 20% of all leukaemias. Whilst there are many clinical and biological similarities between paediatric and adult AML with continuum across the age range, many characteristics of AML are associated with age of disease onset. These include chromosomal aberrations, gene mutations and differentiation lineage. Following chemotherapy, AML cells that survive and result in disease relapse exist in an altered chemoresistant state. Molecular profiling currently represents a powerful avenue of experimentation to study AML cells from adults and children pre‐ and postchemotherapy as a means of identifying prognostic biomarkers and targetable molecular vulnerabilities that may be age‐specific. This review highlights recent advances in our knowledge of the molecular profiles with a focus on transcriptomes and metabolomes, leukaemia stem cells and chemoresistant cells in adult and paediatric AML and focus on areas that hold promise for future therapies. Abstract : Acute myeloid leukaemia (AML) is a clinically and molecularly heterogeneous disease characterised by uncontrolled proliferation, perturbed myeloid differentiation and acquired self‐renewal of hematopoietic stem and myeloid progenitor cells. This review highlights recent advances in our knowledge of the molecular profiles of adult and paediatric AML with a focus on transcriptomes and metabolomes, leukaemia stem cells and chemoresistant cells.